FLIPPED LESSONS MODEL AS AN ATTEMPT TO STRENGTH EFL LEARNERS’ READING COMPREHENSION - Huriyah, Shofiyatul; Contessa, Emilia (Universitas Putera Batam, 2021)
The problem of this study was concerned with the effectiveness of using Flipped Lesson Model in teaching reading comprehension. The objective of this study was to find out whether or not Flipped lesson model was effective to use in teaching reading to the students of English Education Study Program Baturaja University. In this study, pre-experimental method was used. The result it was found mean score of pre-test 48,33 and the mean score of post-test was 61,55 based on calculating of t-test, the value of sign. 0,000 less than the significance level (α = 0,05) the value of tobtained = 11,642 was more than ttable = 1,69 with df 29, and the value of sig. (2-tailed was 0,000). It less then the significance lavel (α = 0,05). Based on the result of t-test had been given, the researcher concluded that it was effective teaching reading by using Flipped Lesson Model to EFL Learners.